Strategy of Poor Family in Facilitating Children to Learn Online during the Covid- 19 Pandemic - Joesa Yolandari; Fatmariza Fatmariza; Azwar Ananda; Yurni Suasti (Budapest International Research and Critics University, 2022)
The purpose of this study is to analyze poor families in facilitating children's online learning. This is a strategy to solve family limitations in facilitating children during online learning. This research is a research with a literature review method. The results of this study can be seen that online learning is considered effective if it can provide convenience not difficulty for poor families, especially in terms of fulfilling children's facilities during the online learning process. There are several strategies that can be used to conduct online learning, including through whatsApp groups, classroom, zoom, facebook and many more. Families are expected to be able to meet the needs of children, especially facilities that support children learning while online so that children learn more effectively.